Students’ Perception Of Application In Writing Of Peer-Assessment: Before And After Revision - Fera Zasrianita; Syukri Hamza; Hadi Winata (Nusantara Education, 2022)
Peer-assessment has attracted more attention an effective assessment tool in recent years. Peer-assessment refers to the arrangement for peers to consider the quality of learning outcomes of others of similar status; it received attention of various studies due to the growing interest in the student-centered approach as learners need to be involved in the learning process even in the assessment. This research was purposed at elaborating students’ perception of application in writing of peer assessment either before or after revision. Writing skills are the skills you use to write effectively and succinctly. A good writer is someone who can communicate their point to their audience without using too much fluff and in a way that the other person can understand. Writing skills don't just include the physical act. If used effectively, peer assessment – a formative assessment strategy that encourages students to comment on the work of their peers – can improve students’ understanding of success criteria, help them to become more engaged in learning and develop their interpersonal skills, as well as potentially even reducing teacher workload. Conversely, however, peer assessment can hinder students’ learning if poor-quality, insensitive or unhelpful peer feedback is exchanged, and may strain relationships between learners. The subject of this research was students in third semester of the English Department of Fakultas Tarbiyah dan Tadris Universitas Islam Negeri Fatmawati Sukarno Bengkulu. The total number was 32 students. The research design used was qualitative research which measured students’ perceptions of the implementation of peer assessment in writing: before and after revision. The result showed that before revision, students had negative perception toward their own writing. After revision, they had positive perceptions toward peer assessment strategy. Those included usefulness and meaningfulness, nature of feedback, reality of feedback, precision, validity, fairness, and personal goal-setting. Besides that, the score after revision (7.9) was higher than the score before revision (6.62). It meant that the result showed the increasing of students’ score after revision.